The Influencing Factors of Teachers’ Job Satisfaction and its Influence on Instructional Practices: Evidence from Korea TIMSS 2019 - Cho, Natthawin (Journal of Multidisciplinary in Social Sciences, 2026)
This study examines the factors influencing teachers’ job satisfaction and its relationship with instructional practices. Drawing on the Job Demands–Resources (JD–R) Theory, the research employs partial least squares structural equation modeling (PLS-SEM) to analyze data from 463 eighth-grade mathematics and science teachers using eTIMSS 2019 data from Korea. Job demands include teacher-related challenges and student-related difficulties. Job resources comprise the school’s emphasis on academic success (from both teachers’ and external perspectives), school environment factors (including safety, student behavior, and school rules), and professional development (both completed and anticipated). Teachers’ job satisfaction and instructional practices are treated as outcome variables. The results indicate that emphasis on academic success, school safety, positive student behavior, and prior professional development are positively associated with higher levels of job satisfaction. Furthermore, a significant relationship is found between teachers’ job satisfaction and their instructional practices. Although student-related challenges, such as disruptive behavior and lack of interest, do not directly affect job satisfaction, teachers continue to express concern about these issues. These findings highlight the importance of supportive school environments and meaningful professional development in enhancing teachers’ job satisfaction and instructional quality. By identifying key determinants of satisfaction, the study offers valuable insights for educational policy and practice. Theoretical and practical implications are discussed, emphasizing the need to strengthen school resources to sustain teacher well-being and instructional effectiveness.